2010
DOI: 10.1097/bth.0b013e3181dcd453
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Volar Digital Defects: Clinical Experience with the Hipothenar Flap

Abstract: Soft tissue defects of the little finger especially for flexor injuries located on area ll, secondary to traumatic loss or contracture of soft tissue, infection or tumor, are challenging procedures for any hand surgeon. The reconstructive goal is to provide stable coverage to all noble structures exposed. Reconstructive options for this particular area include local, regional and free flaps, but all of them offer an important donor site morbidity. We present tree clinical cases of soft tissue defects of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This is another advantage of the island flap compared with the approaches used to treat complex lesions. 12,13 Donor-site closure acts as a temporary splint and extends the fingers. Thus, it contributes to flap adaptation at the recipient site.…”
Section: Discussionmentioning
confidence: 99%
“…This is another advantage of the island flap compared with the approaches used to treat complex lesions. 12,13 Donor-site closure acts as a temporary splint and extends the fingers. Thus, it contributes to flap adaptation at the recipient site.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] The reverse hypothenar flap anatomy has been described earlier, including the number of perforants found and the maximal size of the skin island permitted. [ 1 2 8 9 ] Primary closure of donor site is an advantage compared to many other homodigital flaps. The Allen test is necessary because the ulnar palmar digital vessel is divided at the proximal end and vascularity of the finger entirely depends on the integrity of radial digital vessel.…”
Section: Discussionmentioning
confidence: 99%
“…stated that venous congestion is a disadvantage of hypothenar island flap. [ 1 ] Hao et al . reported that all the flaps survived without complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations